The validity and reliability study of problematic internet use scale for adolescents - Ceyhan, A. Aykut; Ceyhan, Esra (Journal of Dependence, 2014)
Objective: Nowadays, since internet is an important tool in social life, its unhealthy usage may lead to various problems in individuals’ lives. In this framework, various instruments for measuring problematic internet usage and internet addiction are available in literature, but it can be stated that the studies about this subject in Turkey is limited. In Turkey, there are the rapid increase in internet usage in general, and more specifically widespread usage of internet by adolescents and youths for various purposes. Therefore, development of an instrument for understanding the nature of adolescents’ internet usage behaviors has become a necessity. The current study aims to determine psychometric properties of Problematic Internet Usage Scale that was previously developed for university students by Ceyhan, Ceyhan and Gürcan (2007) for adolescents. Method: The present study was carried out with 678 students who attend to the public high schools. Of these students, 571 students who reported that they use the internet more than 2 hours were included in the factor analysis. The data of the study were collected by Problematic Internet Usage Scale and Personal Information Questionnaire. Results: Explanatory and confirmatory factor analyses indicated that scale for adolescents has three subfactors as negative consequences of the internet, excessive use and social benefit/social comfort. The construct with three factors under the 27 items explain the 49.35% of the total variance. Internal consistency of the scale (α) was found as 0.93. Internal consistency coefficients of the three factors were found as 0.93, 0.76 and 0.78, respectively. Conclusion: According to findings, it can be stated that scale is valid and reliable. As a result, so called Problematic Internet Usage ScaleforAdolescents(PİKO-E)wasdeveloped.